Anisotropic Ti-6Al-4V gyroid scaffolds manufactured by electron beam melting (EBM) for bone implant applications. (5th January 2018) - Ataee, Arash; Li, Yuncang; Fraser, Darren; Song, Guangsheng; Wen, Cuie
Highlights: Ti-6Al-4V triply periodic minimal surface lattices are printed by electron beam melting (EBM). As-built scaffolds exhibit structural anisotropy. The mechanical properties of the scaffolds along two orthogonal directions were significantly different. The strain-stress curves of the as-built gyroid scaffolds showed brittle behavior. The ratio of elastic modulus anisotropy in orthogonal directions was comparable to those of trabecular bone. Graphical abstract: Abstract: Ti-6Al-4V gyroid scaffolds with high porosities in the range of 82–85% and three different unit cell sizes 2, 2.5 and 3 mm were manufactured by electron beam melting (EBM) for bone implant applications. The microstructure, mechanical properties and failure mode of the scaffolds with different sample orientations were evaluated. The as-built struts showed orthogonally orientated martensite α′ needles in columnar grains along the building direction with an average hardness of 3.89 GPa and the elastic modulus and yield strength of scaffolds ranged from 637 to 1084 MPa and from 13.1 to 19.2 MPa, respectively. The elastic modulus and yield strength along the build direction and perpendicular to building direction varied by 70% and 49%, respectively, depending on the amount of structural anisotropy and unit cell size. The ratio of elastic modulus anisotropy in orthogonal directions was comparable to those of trabecular bone and could be in favor of bone implant applications. Furthermore, as-built scaffolds showed a mixed mode of ductile and brittle behavior under compression, and the dominant failure mode was by forming orthogonal crush bonds at the peak loads with an angle of 45° with compression axis.